Erosion Behaviour of Chromium Based Hardfacing Alloy - Sandhu, Gaganpreet Singh; Sidhu, Hazoor S.; Chatha, Sukhpal Singh (Asian Review of Mechanical Engineering, 2013)
In the present study commercial available chromium based hardfacing alloy (CPET 071) was deposited on SS304 steel by manual metal arc welding process to investigate the erosion behaviour. Solid particle erosion study was carried out using air jet erosion tester rig. Erosion testing was done at room and 400°C temperature at different impingement angles i.e. 30° and 90°. Optical microscopy technique is used to analyse the microstructure. Microstructure of the deposited hardfacing alloy has been formed to be free from defect such as crakes and porosity, with typical dendritic structure. Erosion rate of the base and hardfaced steel has been found to be higher at 400 °C temperatures with 30° impingement angle.